2015
DOI: 10.1200/jco.2014.56.2439
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Subtypes, PIK3CA Mutation, and the Degree of Benefit From Adjuvant Trastuzumab in the NSABP B-31 Trial

Abstract: Purpose Considerable molecular heterogeneity exists among human epidermal growth factor receptor 2 (HER2) –positive breast cancer regarding gene expression and mutation profiling. Evidence from preclinical, clinical neoadjuvant, and metastatic clinical trials suggested that PIK3CA mutational status and PAM50 intrinsic subtype of a tumor were markers of response to anti-HER2 therapies. We evaluated the predictive value of these two biomarkers in the adjuvant setting using archived tumor blocks from National Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
82
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 27 publications
8
82
4
Order By: Relevance
“…Our present observation is in agreement with these findings. However, unlike the results observed in the neoadjuvant and metastatic settings, there is no association between the PIK3CA mutation and the degree of benefit from transtuzumab in adjuvant setting in the NSABP B-31 trial (43). Although patients with PIK3CA mutations had a slightly poorer DFS and DDFS than those with wild-type in the entire study population (n ¼ 729), the differences did not reach a significance.…”
Section: Discussioncontrasting
confidence: 46%
“…Our present observation is in agreement with these findings. However, unlike the results observed in the neoadjuvant and metastatic settings, there is no association between the PIK3CA mutation and the degree of benefit from transtuzumab in adjuvant setting in the NSABP B-31 trial (43). Although patients with PIK3CA mutations had a slightly poorer DFS and DDFS than those with wild-type in the entire study population (n ¼ 729), the differences did not reach a significance.…”
Section: Discussioncontrasting
confidence: 46%
“…We, similarly to other studies [24,26,28], did not find an association between PIK3CA mutation status and other clinical and biological parameters. However, there are reports in which the correlation between PIK3CA mutations and grade [26] or nodal status (in the ER-positive group) [27] was reported.…”
Section: Discussionsupporting
confidence: 91%
“…In our study we were able to detect 9/75 (12%) tumors with the H1047R mutation and 2/75 (2.7%) with the E545K mutation in the PIK-3CA gene. Our results are comparable to other studies, in which the mutated PIK3CA gene was found in 16%-24% of cases [22][23][24][25][26][27][28]. Comparing data with results obtained by other authors sometimes could be problematic because different mutations are investigated in groups of cancer patients with different clinical characteristics.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations